Phenylalanine and phenylglycine analogues as arginine mimetics in dengue protease inhibitors - Weigel, Lena; Nitsche, Christoph; Graf, Dominik Korbinian; Bartenschlager, Ralf; Klein, Christian D. (Journal of medicinal chemistry, 2015)
Dengue virus is an increasingly global pathogen. One of the promising targets for antiviral drug discovery against dengue and related flaviviruses such as West Nile virus is the viral serine protease NS2B-NS3. We here report the synthesis and in vitro characterization of potent peptidic inhibitors of dengue virus protease that incorporate phenylalanine and phenylglycine derivatives as arginine-mimicking groups with modulated basicity. The most promising compounds were (4-amidino)-l-phenylalanine-containing inhibitors, which reached nanomolar affinities against dengue virus protease. The type and position of the substituents on the phenylglycine and phenylalanine side chains has a significant effect on the inhibitory activity against dengue virus protease and selectivity against other proteases. In addition, the non-natural, basic amino acids described here may have relevance for the development of other peptidic and peptidomimetic drugs such as inhibitors of the blood clotting cascade.
Gesehen am 29.06.2020